2022
DOI: 10.3390/nu14102117
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Anti SARS-CoV-2 Antibodies in Breast Milk from Infected and Vaccinated Women after In Vitro-Simulated Gastrointestinal Digestion

Abstract: Breastfeeding is key for infant development and growth. Breast milk contains different bioactive compounds including antibodies. Recent studies have demonstrated the presence of breast milk SARS-CoV-2 antibodies after maternal infection and vaccination. However, the potential impact on the infant has not been explored yet. As a first step, we aimed at assessing the potential persistence of SARS-CoV-2 IgA and IgG antibodies from infected and vaccinated women in the gastrointestinal tract of the infants by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…32 Similarly, a study of breast milk samples from nursing mothers who received mRNA vaccination against SARS-CoV-2 reported that gastrointestinal digestion of infants significantly decreased the levels of anti-SARS-CoV-2 IgA and IgG. 33 Additionally, a study examining the breakdown of antiphlogistic syncytial virus sIgA/IgA and IgG in human milk from four donors reported a reduction to 33% in the intestinal stage of simulated digestion. 34 The effect on the systemic immune system of breastfed infants is thought to be negligible.…”
Section: Discussionmentioning
confidence: 99%
“…32 Similarly, a study of breast milk samples from nursing mothers who received mRNA vaccination against SARS-CoV-2 reported that gastrointestinal digestion of infants significantly decreased the levels of anti-SARS-CoV-2 IgA and IgG. 33 Additionally, a study examining the breakdown of antiphlogistic syncytial virus sIgA/IgA and IgG in human milk from four donors reported a reduction to 33% in the intestinal stage of simulated digestion. 34 The effect on the systemic immune system of breastfed infants is thought to be negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Breast-milk-derived SARS-CoV-2-specific antibodies have been detected in significant amounts in the breastfeeding infants' saliva and stool, 64,65,68 and studies performed in vitro support the capability of breast-milk-derived anti-SARS-CoV-2 IgG and secretory IgA to resist degradation in the infant gut. 69,70 Importantly, however, anti-SARS-CoV-2 antibodies have not been detected in the blood of infants whose mothers were vaccinated during lactation only, 29,68 suggesting that maternally derived antibodies from breast milk likely do not cross the gut mucosal barrier in detectable quantities. This stands in contrast to antibodies that are transplacentally transferred from mothers vaccinated during pregnancy, which are detectable in the infant's circulation for up to 6 months in the majority of cases.…”
Section: Benefits Of Maternal Covid-19 Mrna Vaccination To the Breast...mentioning
confidence: 99%
“…7 Static models mimicking the infant gastrointestinal tract have been proposed; [8][9][10][11] among those a model has been proposed as an international consensus by INFOGEST participants 12 and has been, since then, used in more than a hundred studies published by the scientific community. [13][14][15][16] Ageing is accompanied by several physiological changes that affect most of the organs of the human body. For example, due to decline in muscular function, impairment in dental status and reduction in salivary flow and modification in composition, there is impairment in oral processing capability which can alter particle size reduction, adversely affecting digestion rate and extent.…”
Section: Introductionmentioning
confidence: 99%
“…7 Static models mimicking the infant gastrointestinal tract have been proposed; 8–11 among those a model has been proposed as an international consensus by INFOGEST participants 12 and has been, since then, used in more than a hundred studies published by the scientific community. 13–16…”
Section: Introductionmentioning
confidence: 99%